2022
DOI: 10.1097/md.0000000000031296
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia of intraoperative nefopam in patients undergoing anterior cervical spine surgery: A prospective randomized controlled trial

Abstract: Background: Nefopam is a non-opioid, non-nonsteroidal anti-imflammatory drug, analgesic drug that inhibits the reuptake of serotonin, norepinephrine, and dopamine. It is widely used as an adjuvant for pain. This study investigated whether the intraoperative, intravenous infusion of nefopam (20 mg) reduces postoperative morphine consumption, pain scores, and alleviates neuropathic pain in patients undergoing cervical spine surgery.Methods: A prospective, paralleled design, randomized study was conducted on 50 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Previous studies investigating the effectiveness of nefopam in patients undergoing spine surgery have yielded mixed results. Some studies have reported that nefopam did not reduce PCA or opioid consumption during the first 3 d post-operation [31][32][33]. In contrast, another study found that the group treated with nefopam experienced less pain during ambulation and had a shorter hospitalization period than the control group [12].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies investigating the effectiveness of nefopam in patients undergoing spine surgery have yielded mixed results. Some studies have reported that nefopam did not reduce PCA or opioid consumption during the first 3 d post-operation [31][32][33]. In contrast, another study found that the group treated with nefopam experienced less pain during ambulation and had a shorter hospitalization period than the control group [12].…”
Section: Discussionmentioning
confidence: 96%
“…There is little evidence to support the use of nefopam in a palliative care setting although trials have been done showing that it reduces the need for postoperative analgesia if given preoperatively3 and intraoperatively 4. In a recent review5 of further surgical studies, nefopam reduced morphine consumption in 8 out 10 studies and also appeared to show synergy with non-steroidal anti-inflammatory drugs or paracetamol.…”
mentioning
confidence: 99%